Quasi coherent state of the Dirac oscillator. Issue 1 (2nd January 2021) - Ghosh, P.; Roy, P.
Abstract : We construct quasi coherent state (QCS) of the ( 1 + 1 ) dimensional Dirac oscillator as eigenstates of matrix annihilation operators. It has been shown that the QCS exhibits non-classical features like quadrature squeezing. It has also been found that for a general complex coherence parameter the quadratures are correlated and the QCS satisfies Schrödinger–Robertson uncertainty relation.